WHO Response to COVID-19 and Technical Support in Uzbekistan: Capacity-building Focus - Kasymova, Nazokat (Asian Pacific Journal of Environment and Cancer, 2020)
The main aim of the present paper is to summarize the WHO efforts on capacity building (or capacity development of health care specialists and medical institutions to improve and retain the skills, knowledge, tools and competencies) both globally and at the national level in Uzbekistan. The joint approach of national governments, international organizations, health care providers and civil society is necessary to assure the effectiveness and quality of the response to the COVID-19 epidemic.